Plasma concentrations of perfluoroalkyl acids and their determinants in youth and adults from Nunavik, Canada - Aker, Amira; Ayotte, Pierre; Caron-Beaudoin, Élyse; Silva, Amila de; Ricard, Sylvie; Gaudreau, Éric; Lemire, Mélanie (Chemosphere, 2022)
Perfluoroalkyl acids (PFAAs), a subset of per- and poly-fluoroalkyl substances (PFAS), are environmentally stable, mobile and bioaccumulative compounds. This leads to high concentrations in wildlife species essential to the cultural identity and subsistence of Arctic populations. Our objective was to characterize the distribution and exposure determinants of PFAAs among Nunavik Inuit adults. The study included up to 1322 Nunavik residents aged 16–80 years who participated in the Qanuilirpitaa? 2017 Nunavik Inuit Health Survey (Q2017). Plasma concentrations were compared to those the general Canadian population using data from the Canadian Health Measures Survey Cycle 5 (2016–2017). Associations between plasma concentrations of nine PFAAs, determined by liquid chromatography-tandem mass spectrometry, and sociodemographic factors and traditional activity participation were examined using multiple linear regression models. Overall exposure to PFAAs was twice as high compared to the general Canadian population and less regulated perfluorononanoic acid (PFNA) and perfluoroundecanoic acid (PFUnDA) concentrations were 7-fold higher, and perfluorodecanoic acid (PFDA) concentrations were 4-fold higher. Males had higher concentrations of perfluorooctanoic acid (PFOA) and perfluorohexane sulfonate (PFHxS), whereas females had higher concentrations of PFDA and PFUnDA. PFAAs concentrations increased with age and were highest among those aged 60+ years. PFNA and PFOA